Physiological concept of plyometric training to improve physical fitness of basketball players: a systematic review - Baskoro Nugroho Putro; Junian Cahyanto Wibawa; Novadri Ayubi; Procopio B. Dafun Jr; Jiang Wen Ming (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Increasing the physical capacity of basketball players is needed to support achievement. Good physicality is closely correlated with the resulting exercise performance. Plyometric exercise is an exercise to develop speed and strength (power) by using your own body weight.